2020
DOI: 10.1177/0961203320947154
|View full text |Cite
|
Sign up to set email alerts
|

“APS pregnancy – The offspring”

Abstract: Background Antiphospholipid antibody syndrome (APS) is an autoimmune disease that affects women in childbearing age. In recent years, great improvements were achieved in the management of pregnancies in these women. Prematurity could be an issue in these pregnancies, mainly due to the direct pathogenic effect of antiphospholipid antibodies (aPL) on the placental surface. Maternal IgG aPL can cross the placenta and theoretically interact with the growing fetus; it could reach the fetal brain because of the inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…A study in healthy children with no transplacental transfer of pathogenic antibodies found that 48% showed positivity for anti-b2G1 IgG antibodies which peaked at 6 months of age and then progressively decreased. 8 Although similar associations were not found for the other aPLs tested, this highlights an interesting potential pathway for the synthesis of de novo aPLs in neonates and foetuses.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…A study in healthy children with no transplacental transfer of pathogenic antibodies found that 48% showed positivity for anti-b2G1 IgG antibodies which peaked at 6 months of age and then progressively decreased. 8 Although similar associations were not found for the other aPLs tested, this highlights an interesting potential pathway for the synthesis of de novo aPLs in neonates and foetuses.…”
Section: Discussionmentioning
confidence: 51%
“…Inflammation in the period before birth has been found to affect the pool of peripheral regulatory T cells in the cord blood of premature infants, thereby potentially affecting the development and function of the innate and adaptive immune systems. 8 In these premature infants, the immune system effects and newly-synthesised aPLs may act as the two ‘hits’. In the present case, the mother had gestational hypertension, which may have acted as a risk factor for foetal thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the baby was born growth-restricted, which is also incriminated in the causation of thrombosis by some authors, especially in babies with underlying prothrombotic conditions 7. Another important aspect is the maternal presence of autoantibodies like antiphospholipid antibodies, which can also predispose neonates to thrombosis, suggesting a need to screen such babies for the same in the neonatal period 8…”
Section: Discussionmentioning
confidence: 68%